Ermittlung der Nachfrage nach ok̈ologischen Guẗern der Landwirtschaft; Das Northeim-Projekt - The demand for ecological goods in decentralised agri-environmental payment schemes - Anke Fischer; Sonja K. Hespelt; Rainer Marggraf (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– This paper presents a case study on the development and implementation of a decentralised and outcome-based agri-environmental payment scheme in a project region in central Germany. A research group from Goettingen University together with local actors designed the scheme which complies with the European Union's Common Agricultural Policy. The core of the programme is the creation of a market for ecological goods, in this case: of plant diversity standards in agriculture. Supply is provided by the local farmers, who, in an open competitive bidding, offer to produce as much as they are willing to of the commodity in question. The local population has to be seen as the beneficiary of these environmental goods. In the project, it is represented by a Regional Advisory Board which expresses the demand for plant diversity (i) by defining the goods and (ii) by allocating the funds to the respective goods. Hence, these plant diversity goods are treated as merit goods. To justify this approach, results from a contingent valuation study that focused on the respondents' decision behaviour are applied. These results show that the utility expected from the provision of these goods is substantial and that ecological goods are considered as personally relevant. Based on these findings, the paper discus-ses the provision of ecological goods as merit - as opposed to private - goods.
Keywords: 330; Öko-Produkt; Agrarprodukt; Meritorische Güter; Zahlungsbereitschaftsanalyse